(3GdehGLgI GdJTQjYjI dLQjeI GdEJLGQ HGdHTQ ai GdbGfhf GdCQOfi h GdebGQf (B/ s - (3aQGS QajaGf OgjeT Hfi YHOGdQMefs; (3CMeO YhV HdGd s; (3YGOd jMjis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3JYO LQjeI GdGJLGQ HGdHTQ GdUhQI GdMOjKI dXGgQI GdQb Ch GdYHhOjI(B: (3h gi LQjeI PGJ NWhQI YGdejI JJQJH YdjgG CKGQ GLJeGYjI h UMjI h GbJUGOjI h ZjQgG ef CKGQ NWjQI(B. (3h dPdc abO OCH GdeLJeY GdOhdi Ydi GdGgJeGe HecGaMI gPg GdLQjeI GdHTYI h GdMO efgG h bO SGgeJ GdefXeGJ GdOhdjI h GdEbdjejI ai hVY GdYOjO ef GdehGKjb GdOhdjI h GdEbdjejI h EUOGQ YOO ef GdOhd JTQjYGJ NGUI decGaMI gPg GdLQjeIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2019s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B331-364s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdEJLGQ HGdHTQ s; (3GdESJZdGd GdLfSi s; (3GdQb(B-(3GdYHhOjIs; (3GSHGH GdGJLGQ HGdHTQ s; (3LQjeI JgQjH GdegGLQjf s; (3GdSNQI aj LQjeI GdGJLGQ HGdHTQ s; (3fRY GdGYVGA GdHTQjg s; (3GdGSJZdGd GdLfSj aj LQjeI GdGJLGQ HGdHTQ s; (3GdGSJQbGb h GdGSJYHGO aj LQjeI GdGJLGQ HGdHTQ s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs